Environmental DNA reflects common haplotypic variation - Clare I. M. Adams; Christopher Hepburn; Gert‐Jan Jeunen; Hugh Cross; Helen R. Taylor; Neil J. Gemmell; Michael Bunce; Michael Knapp (Environmental DNA, 2023)
Abstract Analysis of environmental DNA (eDNA) has gained widespread usage for taxonomically based biodiversity assessment. While interest in applying noninvasive eDNA monitoring for population genetic assessments has grown, its usage in this sphere remains limited. One barrier to uptake is that the effectiveness of eDNA detection below the species level remains to be determined for multiple species and environments. Here, we test the utility of this emergent technology to obtain within‐species haplotypic variation of New Zealand (NZ) blackfoot pāua (Haliotis iris). We compare mitochondrial haplotype diversity recovered from marine eDNA samples against traditional tissue samples of blackfoot pāua collected at the same NZ coastal site. Targeting the ATP8‐ATP6 region, we recovered four mitochondrial haplotypes from eDNA versus six haplotypes from tissue samples. Three common haplotypes were recovered with both eDNA and tissue samples, while only one out of three rare haplotypes – represented in tissue samples by one individual each – was recovered with our eDNA methods. We demonstrate that eDNA monitoring is an effective tool for recovering common genetic diversity from pāua, although rare (<5%) haplotypes are seldom recovered. Our results show the potential of eDNA to identify population‐level haplotypic diversity for gastropods in the marine environment below the species level. This work demonstrates that eDNA methods can be an effective, noninvasive tool for genetic monitoring. Noninvasive eDNA sampling could minimize target organism stress and human interaction enabling population genetic research for hard‐to‐sample, delicate, or sensitive species.